2006
DOI: 10.1007/s00442-006-0499-8
|View full text |Cite
|
Sign up to set email alerts
|

Body size changes among otters, Lutra lutra, in Norway: the possible effects of food availability and global warming

Abstract: Using museum data of adult specimens whose sex, age, and locality are known, we studied temporal and geographical body size trends among the otter, Lutra lutra, in Norway. We found that body size of the otters increased during the last quarter of the twentieth century, and suggest that this trend is related to increased food availability from fish farming and possibly also to energy saving due to elevated sea temperatures. Birth year and death year explained 38.8 and 43.5%, respectively, of the variation in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 22 publications
2
40
0
Order By: Relevance
“…It is well known that conditions experienced during early development, particularly food quantity and quality, affect growth, and ultimately adult body size (Bolton et al 1982;Lindström 1999;Yom-Tov et al 2006;Hersteinsson et al 2009). Yom-Tov et al (2010) have shown that this is the case also for the lynx in Sweden, where roe deer density at birth year affects body size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that conditions experienced during early development, particularly food quantity and quality, affect growth, and ultimately adult body size (Bolton et al 1982;Lindström 1999;Yom-Tov et al 2006;Hersteinsson et al 2009). Yom-Tov et al (2010) have shown that this is the case also for the lynx in Sweden, where roe deer density at birth year affects body size.…”
Section: Discussionmentioning
confidence: 99%
“…This effect of latitude may be explained as a Bergmannian reaction to ambient temperature, with females being more sensitive to environmental conditions than males. Bergmannian trend in body size was also detected among otters (Lutra lutra) in Norway, and was interpreted as a reaction to ambient temperature (Yom-Tov et al 2006). However, in Sweden, the size of lynx increases with The best two (females) and four (males) models, selected by the Akaike information criterion (AIC), are presented.…”
Section: The Effect Of Latitudementioning
confidence: 92%
“…Only in some exceptional cases, the opposite trend is observed, with increasing body sizes for certain fish, lizards, birds and mammals. Along this line, studies such as those by Yom-Tov and collaborators [21,22] have shown an increase in body size in medium and small mammals (otters and shrews, respectively), with increasing temperatures during the last decades. The hypothesized mechanism behind this was an increase in productivity over the whole ecosystem owing to increasing temperatures, which in turn facilitated an increase in species body size.…”
Section: Closed Communitiesmentioning
confidence: 91%
“…In addition to these large-scale patterns, human activities occurring at the local scale may also affect body condition and size (e.g. body size of Otters Lutra lutra increased in Norway in response to expanding fish farming; Yom-Tov et al 2006b; carnivores benefiting from human garbage; Yom-Tov 2003). Agricultural practices are known to have strongly benefited some goose populations by means of improved feeding opportunities, leading to better body condition and increased abundance (e.g.…”
Section: Introductionmentioning
confidence: 99%